2016
DOI: 10.1037/fam0000147
|View full text |Cite
|
Sign up to set email alerts
|

Preventing adolescent depression with the family check-up: Examining family conflict as a mechanism of change.

Abstract: Family-centered prevention programs are understudied for their effects on adolescent depression, despite considerable evidence that supports their effectiveness for preventing escalation in youth problem behavior and substance use. This study was conducted with 2 overarching goals: (a) replicate previous work that has implicated the Family Check-Up (FCU), a multilevel, gated intervention model embedded in public middle schools, as an effective strategy for preventing growth in adolescent depressive symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 51 publications
2
26
0
2
Order By: Relevance
“…Further, in a longitudinal study, Dishion and colleagues (2010) 62 showed that cascading peer dynamics might contribute to the progression of problem behavior to violence, thus indicating the importance of improving the peer context during early adolescence. A final example includes a trial with the FCU evaluating family conflict in the prevention of adolescent depression 21 . Families with children in middle school, randomized to the FCU reported less increases in child depressive symptoms and family conflicts from 6 th to 9 th grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in a longitudinal study, Dishion and colleagues (2010) 62 showed that cascading peer dynamics might contribute to the progression of problem behavior to violence, thus indicating the importance of improving the peer context during early adolescence. A final example includes a trial with the FCU evaluating family conflict in the prevention of adolescent depression 21 . Families with children in middle school, randomized to the FCU reported less increases in child depressive symptoms and family conflicts from 6 th to 9 th grade.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis on prevention programs 7 and the Blueprints for Healthy Development and SAMHSA’s National Registry of Evidence-based Programs and Practices, a family-based program, the Family Check-Up (FCU 15 ), is also described to have a good evidence-base. The FCU is a second generation of parent training programs 16 – 19 , with effects on reductions of externalizing behavior problems 20 , substance use 18 , and prevention of child depression 21 . The FCU is based on the Oregon PMT-model but has been designed to be ecologically more valid as it is tailored to the needs and motivation of families, grounded in a structured assessment and feedback phase during the first three sessions.…”
Section: Introductionmentioning
confidence: 99%
“…It means that the importance of family is the core feature for most Chinese people. Previous studies have shown that the family environment can directly affect the emotions in family members, especially the dimension of cohesion ( Harris and Zakowski, 2003 ; Burnett et al, 2017 ), expressiveness ( Luebbe and Bell, 2014 ), and conflict ( Yap et al, 2014 ; Yap and Jorm, 2015 ; Fosco et al, 2016 ). However, whether the family environment has an effect on the mental health of medical staff during the epidemic is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Auerbach et al reported that family conflict was prospectively related to greater depressive symptoms among Canadian adolescents [6]. Fosco et al also found that increasing levels of family conflict during middle school was associated with higher levels of depressive symptoms in adolescents [7]. However, previous studies largely focused on the overall family conflict in Western countries, while little consideration has been given to the specific influence of mother-adolescent conflict and father-adolescent conflict in Asian countries like China.…”
Section: Introductionmentioning
confidence: 99%